The effect of breed, season and age of bulls on the quantity and quality of fresh bull semen - Munusamy, Vegrashrma (2014)
The primary objectives of this study were to evaluate the effect of breed, season and age on quantity and quality parameters of fresh bull's semen. A total of 168 samples of bull's ejaculate were analysed for this study consisting of Bali, Brahman, Charolais, Jersey, Limousin, Mafriwal and Piedmontese breeds. The age of bulls ranged from 46 to 112 months. By utilizing artificial vagina, the collection of semen was carried out in both dry and rainy season. Volume of semen samples, sperm concentration, percentage of motile spermatozoa and percentage of progressive motility spermatozoa were evaluated immediately after collection. By performing Duncan's Multiple Range Test, the difference between any two mean was evaluated. The result of the study indicated that breed affected the volume of semen very significantly (P<0.01), whereby Limousin (7.33 ± 0.358) was found to be the best performer among all the 7 breeds while Piedmontese (3.21 ± 0.369) was found to have the lowest amount of ejaculate. The result obtained shows that breed affected total sperm concentration very significantly (P<0.01). Brahman (786.88 ± 141.450) was reported to possess the highest total sperm concentration and Charolais (407.84 + 82.791) produced ejaculate with the lowest total sperm concentration. Results also indicate that the sperm motility was significantly affected by breed (P<0.05), whereby Brahman (91.20 ± 3.891) was reported to produce semen output with highest sperm motility while Piedmontese (73.33 ± 9.728) was found to have lowest sperm motility. Breed was found to affect progressive motility of spermatozoa very significantly (P<0.01). The influence of season on volume of semen and sperm motility was found to be not significant (P>0.05). Meanwhile, season indicated that there was highly significant effect (P<0.01) on total sperm concentration and progressive motility of spermatozoa. Age of bulls shows no significant (P>0.05) effect on volume of semen, sperm motility and progressive motility of spermatozoa. Meanwhile, effect of age of bulls was found to be significant (P<0.05) on total sperm concentration. It is recommended that breed, season and age chosen to conduct semen collection is given particular attention to obtain the best possible semen quantity and quality.